2014
DOI: 10.1016/j.expneurol.2014.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Neurologic impairment following closed head injury predicts post-traumatic neurogenesis

Abstract: In the mammalian hippocampus, neurogenesis persists into adulthood, and increased generation of newborn neurons could be of clinical benefit following concussive head injuries. Post-traumatic neurogenesis has been well documented using “open” traumatic brain injury (TBI) models in rodents; however, human TBI most commonly involves closed head injury. Here we used a closed head injury (CHI) model to examine post-traumatic hippocampal neurogenesis in mice. All mice were subjected to the same CHI protocol, and a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 49 publications
2
21
0
Order By: Relevance
“…The age-related decline in neurogenesis is also accompanied by an age-related decline in cognitive function (Bolognin et al, 2014). Alterations in hippocampal neurogenesis have also been reported in a number of neurodegenerative diseases (AD and Huntington's disease) (Choi et al, 2014a;Moon et al, 2014;Perry et al, 2012), neurological diseases (epilepsy, ischaemia and traumatic brain injury) (D'Alessio et al, 2015;Matsuda et al, 2015;Villasana et al, 2014) and neuropsychiatric conditions (stress and depression) (Boldrini et al, 2012;Lucassen et al, 2015;Miller and Hen, 2015). Deficits in cognitive function have also been reported in some of these conditions.…”
Section: Adult Hippocampal Neurogenesis and Cognitive Functionmentioning
confidence: 97%
“…The age-related decline in neurogenesis is also accompanied by an age-related decline in cognitive function (Bolognin et al, 2014). Alterations in hippocampal neurogenesis have also been reported in a number of neurodegenerative diseases (AD and Huntington's disease) (Choi et al, 2014a;Moon et al, 2014;Perry et al, 2012), neurological diseases (epilepsy, ischaemia and traumatic brain injury) (D'Alessio et al, 2015;Matsuda et al, 2015;Villasana et al, 2014) and neuropsychiatric conditions (stress and depression) (Boldrini et al, 2012;Lucassen et al, 2015;Miller and Hen, 2015). Deficits in cognitive function have also been reported in some of these conditions.…”
Section: Adult Hippocampal Neurogenesis and Cognitive Functionmentioning
confidence: 97%
“…Studies from our lab and others have shown that TBI significantly increases cell proliferation in both the SVZ and DG in adult mice and rats in varying TBI models including fluid percussive injury (FPI) (Chirumamilla et al, 2002; Rice et al, 2003), controlled cortical impact injury (CCI) (Dash et al, 2001; Gao et al, 2009), closed head weight drop injury (Villasana et al, 2014) and acceleration-impact injury (Bye et al, 2011). Common to all reported TBI models, the most prominent endogenous cell response in both the DG and SVZ following TBI is an increase in cell proliferation.…”
Section: Tbi-induced Neurogenesis In Experimental Studies In Tbi Animmentioning
confidence: 99%
“…As for the degree of neuronal differentiation, different results have been reported. In diffuse injury models such as the closed head weight drop model and the fluid percussion model, an increased total number of new neurons in the subgranule zone and granule cell layer of the DG were observed following injury (Sun et al, 2007; Villasana et al, 2014). Whereas in a focal injury model such as CCI, the number of new neurons generated following TBI was not significantly increased as compared to sham control despite enhanced cell proliferation (Gao and Chen, 2013).…”
Section: Tbi-induced Neurogenesis In Experimental Studies In Tbi Animmentioning
confidence: 99%
See 1 more Smart Citation
“…12,[24][25][26] Notably, the severity and/or type of injury was found to impact differential changes in hippocampal neurogenesis, 12 and altered neurogenesis was found to be associated with cognitive impairment. [27][28][29] Interestingly, Robinson et al 11 used the same model as in the current study and found no significant differences in the DCX-labeled cells in the dentate gyrus at 30 d after an FPI. 11 There are several possible explanations for this discrepancy.…”
Section: Discussionmentioning
confidence: 99%